A revised classification of the fluvicoline tyrant flycatchers (Passeriformes, Tyrannidae, Fluvicolinae) - Ohlson, Jan I.; Irestedt, Martin; Filho, Henrique Batalha; Ericson, Per G. P.; Fjeldså, Jon (Zootaxa, 2020)
A new classification is proposed for the subfamily Fluvicolinae in the New World Flycatchers (Tyrannidae), based on the results of a previously published phylogeny including more than 90% of the species. In this classification we propose one new family level name (Ochthoecini) and one new generic name (Scotomyias). We also resurrect three genera (Heteroxolmis, Pyrope and Nengetus) and subsume five (Tumbezia, Lathrotriccus, Polioxolmis, Neoxolmis and Myiotheretes) into other genera to align the classification with the current understanding of phylogenetic relationships in Fluvicolinae.